Spray characteristics of diesel-CNG dual fuel jet using schlieren imaging technique - Ismael, M.A. (Trans Tech Publications Ltd, 2014)
Natural gas is a low cost fuel with high availability in nature. However, it cannot be used by itself in conventional diesel engines due to its low flame speed and high ignition temperature. The addition of a secondary fuel to enhance the mixture formation and combustion process facilitate its wider use as an alternative fuel. An experimental study was performed to investigate the diesel- CNG dual fuel jet characteristics such as: jet tip penetration, jet cone angle and jet tip velocity. A constant-volume optical chamber was designed to facilitate maximum optical access for the study of the jet macroscopic characteristics at different injection pressures and temperatures. The bottom plate of the test rig was made of aluminum (piston material) and it was heated up to 500 K at ambient pressure. An injector driver was used to control the single-hole nozzle diesel injector combined with a natural gas injector. The injection timing of both injectors were synchronized with a camera trigger. Macroscopic properties of diesel and diesel-CNG dual fuel jets were recorded with a high speed camera using the Schlieren imaging technique and associated image processing. Measurements of the jet characteristics of diesel and diesel-CNG dual fuel are compared together under evaporative and non-evaporative conditions as well as different injection pressures are presented in this paper. Â© (2014) Trans Tech Publications, Switzerland.